1998
DOI: 10.1103/physreva.58.1545
|View full text |Cite
|
Sign up to set email alerts
|

Observation of transient electromagnetically induced transparency in a rubidium Λ system

Abstract: Observation of transient effects in electromagnetically induced transparency ͑EIT͒ is reported in Rb 85 cooled in a magneto-optical trap. The transmission of a weak probe beam in resonance with the 5S 1/2 (Fϭ3) to 5P 3/2 (Fϭ3) hyperfine transition increased transiently when a relatively strong coupling field in resonance with the 5S 1/2 (Fϭ2) to 5 P 3/2 (Fϭ3) hyperfine transition was switched on rapidly using a Pockels cell. The probe transient showed an initial Rabi half-cycle overshoot before settling down t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 10 publications
2
36
0
Order By: Relevance
“…This behaviour of the system is related to the one predicted [3] and experimentally observed [4] in a typical three level Λ-type atomic system which exhibits electromagnetically induced transparency through the application of a coupling laser field. The difference in our case, is that the transparency and the transient gain without inversion occur due to the coupling to a radiation reservoir with an inverse square-root singularity of the density of modes at threshold and are not induced by an external laser field.…”
supporting
confidence: 75%
“…This behaviour of the system is related to the one predicted [3] and experimentally observed [4] in a typical three level Λ-type atomic system which exhibits electromagnetically induced transparency through the application of a coupling laser field. The difference in our case, is that the transparency and the transient gain without inversion occur due to the coupling to a radiation reservoir with an inverse square-root singularity of the density of modes at threshold and are not induced by an external laser field.…”
supporting
confidence: 75%
“…This phenomenon is known as electromagnetically induced transparency (EIT) [1][2][3]. In recent years, many studies on EIT and related phenomena have been carried out, which reveal the importance of EIT in understanding the fundamental physics involving interactions between light field and resonant medium [4][5][6][7][8]. It has been shown that EIT may have applications in a variety of research topics such as quantum optics with slow photons [9][10][11][12][13], quantum information processing [14], atomic frequency standard [15][16][17][18], and quantum nonlinear optics [19,20].…”
Section: 50gy 32802tmentioning
confidence: 99%
“…There have been several multi-mode treatments of EIT, which examine the transients due to switching on optical fields [15,16] as well as of sudden changes in two-photon (Raman) resonance [17,18]. In addition, the transient properties of the associated nonlinearities, both absorptive (photon switching) [19,20] and dispersive (cross-Kerr effect) [21][22][23][24][25] have since been investigated.…”
Section: Introductionmentioning
confidence: 99%